SUBJECTIVE HAPPINESS, ENTREPRENEURSHIP EDUCATION, AND ENTREPRENEURIAL INTENTIONAMONG HIGHER EDUCATION STUDENTS - Fitriana, Nina; Kassymova, Gulzhaina Kuralbaevna (Insight: Jurnal Ilmiah Psikologi, 2021)
This study aims to determine the relationship between subjective happiness and higher education students’ entrepreneurial intentions. In addition, the objective of this study is to find out whether entrepreneurship education was correlated with entrepreneurial intention of higher education student. Entrepreneurial activities are carried out as a way to overcome unemployment. One of the things that influence entrepreneurial behavior is entrepreneurial intention. Initiation and support for starting new businesses is an important task of policymakers as well as academics. Thus, higher education institutions play a very important role in developing entrepreneurial intention.  However, several previous studies stated that higher education students had low entrepreneurial intentions. Thus, research on entrepreneurial intentions among students is important to be conducted. This study examines entrepreneurial intentions and the factors that influence it, namely subjective happiness, family work background, and entrepreneurship education. The measuring instruments used in this study are the Subjective Happiness Scale and the Entrepreneurial Intention Scale which refers to the theory of planned behavior which states that intention can be seen from personal attitudes, social norms, and assessment of controlled behavior. The subjects of this study were 80 students, with particular subject characteristics such as 6th semester students who are enrolled in higher education institutions. The data analysis technique used is the Product Moment correlation test and the Independent Samples T-Test. The results of this study indicate that there is a positive relationship between subjective happiness and student entrepreneurial intentions. Thus, it can be stated that the higher the level of one's subjective happiness, the higher the entrepreneurial intention. In contrast, the lower a person's subjective happiness level, the lower his or her entrepreneurial intention of higher education students. This study also found that there is no relationship between entrepreneurship education and entrepreneurial intention of higher education students. This research can be a recommendation for higher education institution to boost subjective happiness of students in order to increase the student entrepreneurial intentions.